Effect of Embryo Transfer Seven Days after Artificial Insemination with Sexed and Conventional Semen from Superovulated Cattle - Enkhbolor Barsuren; Sang Hwan Kim; Ho-Jun Lee; Jong Taek Yoon (The Korean Society of Animal Reproduction and Biotechnology, 2019)
Sexed sperm can contribute to increase the profitability of the cow industry through the production of offspring of the craved sex, such as males for meat or females for dairy production. Therefore, the utilization of sexed sperms plays a very important role in the production of offspring of superior cattle. In this study, we examined the pregnancy rates and calves sexing proportion of male and female calves produced using AI, both performed using sexed and conventional sperm. In the result, the conception rates after ET were 73.3% (33/45) sexed semen and 52% (55/104) conventional semen. Thus, the sex ratio for sexed-semen inseminations was 70% (21/30) females for singleton births within a 272 to 292 day gestation interval. The sex ratio for conventional semen was 61% (34/56) females for births. As a result, it is suggested that the use of sex classification sperm will play a very important role in the offspring production of Korean bovine.